Tantalum boride as a biocompatible coating to improve osteogenesis of the bionano interface. Issue 8 (9th April 2020) - Li, Ruiyan; Liu, Guancong; Yang, Lina; Qing, Yun'an; Tang, Xiongfeng; Guo, Deming; Zhang, Kan; Qin, Yanguo
Abstract: A proper biological microenvironment conducive to tissue repair and regeneration, while the bioimplant interface directly affects the local microenvironment. In this study, to improve the biological microenvironment, a nanosized tantalum boride (Ta‐B) was coated on a titanium alloy substrate (Ti6Al4V, TC4) using magnetron cosputtering. The sample surface was characterized by X‐ray diffraction (XRD) and transmission electron microscopy (TEM). To investigate the effects of tantalum boride coating on the microenvironment, rabbit bone marrow stromal cells (BMSCs), and RAW 264.7 cells were respectively seeded on the sample surface and relevant experiments were conducted in vitro. The pure tantalum coating (Ta) and naked TC4 were prepared as controls. Our results showed that the Ta‐B coating enhanced cell proliferation and adhesion and inhibited the inflammatory response. Findings of alkaline phosphatase (ALP) staining, alizarin red staining and real‐time PCR for osteoblastic gene expression indicated that Ta‐B and Ta coating improve the osteogenesis, in which Ta‐B coating showed higher osteogenesis than Ta coating. Thus, this study suggests that Ta‐B coating with excellent biocompatibility could have new applications for wound healing in bone tissue engineering.